PENGARUH KEPEMIMPINAN NEGARA - NEGARA DI ASIA DALAM REFORMASI BIROKRASI INDONESIA - Munir, Fitrisia (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
This paper cites a bit of the old bureaucratic concept developed by a social scientist, Max Weber. Max Weber {1864-1920) describes bureaucracy as influential organizational design as an abstract system for solving rational state management problems without any friction caused by human error and emotion. According to Weber, "bureaucratic organizations are the most rational means to exercise imperative control over human beings". 'The bureaucratic theory is based on the nature of the relationship of authority within the organization. This is related to how organizations actually operate rather than how they should function. Weber visualized the bureaucratic model as an orderly arrangement of forces to achieve rational human behavior under a professional hierarchy. In this case, bureaucracy is now a milestone for running a competitive State and developing in terms of a leader's mindset towards his community towards good governance. Bureaucracy reform began in 1998 as an institutional initiative that increased to the national level in 2008. Bureaucratic reforms are needed to achieve good & clean governance, free from corruption, collusion and nepotism (KKN), improve the quality of public services, increase capacity and accountability Performance. The bureaucracy should result in professionalism of the apparatus supported by recruitment of personnel and the promotion of competence-based, transparent, and capable of encouraging the mobility of personnel between regions, between centers, and between centers and regions, as well as earning salaries and other forms of welfare. The emergence of bureaucratic reforms in each of the countries in Asia has resulted in a tight chance of individual countries to compete to run the governmental wheels based on rational legal authorities. Every leader of a State is demanding to be firm and able to balance their situation and perspective in overcoming their country's problems. The failure of the bureaucracy is seen from the leadership that lacks the reformist figures but instead makes a role model who hopes to make a difference. Instead, the bureaucracy can only be said to succeed if it can improve the quality of service on the one hand, while creating a clean and accountable government on the other.